The Three Axial Perineal Evaluation (TAPE) score: a new scoring system for comprehensive evaluation of pelvic floor function. (June 2014) - Altomare, D. F.; Di Lena, M.; Giuratrabocchetta, S.; Giannini, I.; Falagario, M.; Zbar, A. P.; Rockwood, T.
Abstract Aim Abnormalities of one pelvic floor compartment are usually associated with anomalies in the other compartments. Therapies which specifically address one clinical problem may potentially adversely affect other pelvic floor activities. A new comprehensive holistic scoring system defining global pelvic function is presented. Method A novel scoring system with a software program is presented expressing faecal, urinary and gynaecological functions as a geometric polygon based on symptom‐specific questionnaires [the three axial pelvic evaluation (TAPE) score] where differences in overall geometric area vary from normal. After validation in healthy volunteers, its clinical performance was tested on patients with obstructed defaecation, genital prolapse and urinary/faecal incontinence treated by the stapled transanal rectal resection (STARR) procedure, colpo‐hysterectomy and sacral nerve modulation, respectively. The TAPE score was correlated with the Pelvic Floor Impact Questionnaire 7 quality of life score. Results There was good inter‐observer variation and internal consistency between two observers recording the TAPE score in normal volunteers. In the STARR patients, constipation improved but the TAPE score was unchanged because of deterioration in other pelvic floor functions leading to an unchanged overall postoperative recorded quality of life. Conversely, incontinent patients treated with sacral nerve stimulation improved their function showing concomitant improvements in TAPE scores and quality of life indices. Similar correlative improvements were noted in patients undergoing hysterectomy for genital prolapse. Conclusion The TAPE score defines the impact of symptom‐specific treatments on the pelvic floor and may provide an opportunity for comparison of clinical data between units and in clinical trials of specific medical and surgical pelvic floor management.